Distribusi Spasial dan Faktor Kontaminasi Logam Berat di Pesisir Kota Makassar - Rahmat Januar Noor; Arnold Kabangnga; Fathuddin Fathuddin (Jurnal Kelautan Tropis, 2021)
The presence of heavy metals in coastal waters is a threat to the wealth of coastal ecosystems because they are toxic. The people activities of Makassar City are centered in the coastal area so that they have the potential to produce heavy metal pollutants that can escape into coastal waters. This study aimed to determine the distribution of heavy metal concentrations in the sediment and water column and to determine the contamination factor. The research location is along the coast of Makassar City by determining the location of the observation based on potential sources of input, namely ports, river estuaries, and tourism activities. The research method used survey methods with in-situ measurements (oceanographic parameters) and ex-situ (heavy metal concentrations) and data presentation using tables, graphs, and analysis of variance test results. The concentration of heavy metals Pb, Cd, and Zn in the sediment were higher and significantly different (p <0.05) compared to the water column, while Cu not different. There was no significant difference in the concentration of heavy metals (p> 0.05) spatially (ports, river estuaries, tourist sites). Heavy metals in the sediments did not exceed the quality standard, while several heavy metals in the water column exceeded the quality standards, namely Pb and Cd. The contamination level of heavy metal pollutants studied in the coastal waters of Makassar City was low (CF <1), and if sorted, a pattern of heavy metal was Cd> Zn> Pb> Cu. Keberadaan logam berat di perairan pesisir merupakan ancaman bagi kekayaan ekosistem pesisir sebab bersifat toksik. Aktivitas masyarakat Kota Makassar berpusat di daerah pesisir sehingga berpotensi menghasilkan bahan pencemar logam berat yang dapat lepas ke perairan pesisir. Penelitian ini bertujuan untuk mengetahui distribusi konsentrasi logam berat di sedimen dan kolom air serta menentukan faktor kontaminasi. Lokasi penelitian di sepanjang pesisir Kota Makassar dengan penentuan lokasi pengamatan berdasarkan potensi sumber masukan yaitu pelabuhan, muara sungai, dan aktivitas wisata. Metode penelitian menggunakan metode survey dengan pengukuran secara insitu (parameter oseanografi) dan exsitu (konsentrasi logam berat) serta penyajian data menggunakan tabel, grafik, dan hasil pengujian analisis varians. Konsentrasi logam berat Pb, Cd, dan Zn pada sedimen lebih tinggi serta berbeda secara signifikan (p<0,05) dibandingkan dengan kolom air sedangkan Cu tidak berbeda. Tidak terdapat perbedaan konsentrasi logam berat yang nyata (p>0,05) secara spasial (pelabuhan, muara sungai, lokasi wisata) Logam berat pada sedimen tidak melampaui baku mutu sedangkan pada kolom air terdapat beberapa logam berat yang melampaui baku mutu yaitu Pb dan Cd. Tingkat kontaminasi bahan pencemar logam berat yang diteliti di perairan pesisir Kota Makassar termasuk rendah (CF<1) dan bila diurutkan maka ditemui pola Cd>Zn>Pb>Cu.